Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/onc.2016.490
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 recruits nuclear Aurora kinase A to participate in a positive feedback loop essential for the self-renewal of breast cancer stem cells

Abstract: Substantial evidence suggests that breast cancer initiation, recurrence and drug resistance is supported by breast cancer stem cells (BCSCs). Recently, we reported a novel role of Aurora kinase A (AURKA) in BCSCs, as a transactivating co-factor in the induction of the c-Myc oncoprotein. However, the mode of action and transcriptional network of nuclear AURKA in BCSCs remain unknown. Here, we report that nuclear AURKA can be recruited by Forkhead box subclass M1 (FOXM1) as a co-factor to transactivate FOXM1 tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 46 publications
3
93
1
1
Order By: Relevance
“…High FOXM1 expression was detected in CSCs and TICs. FOXM1 promoted the proliferation and maintenance of breast [28,43], hepatocellular [44], pancreatic [45], and lung CSCs [46], and FOXM1 depletion repressed the stemness of these cancer cells. FOXM1 is an important component of the reprogramming network and functions together with reprogramming transcriptional factors, such as OCT4, SOX2, and KLF4, to regulate CSC self-renewal and maintenance [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High FOXM1 expression was detected in CSCs and TICs. FOXM1 promoted the proliferation and maintenance of breast [28,43], hepatocellular [44], pancreatic [45], and lung CSCs [46], and FOXM1 depletion repressed the stemness of these cancer cells. FOXM1 is an important component of the reprogramming network and functions together with reprogramming transcriptional factors, such as OCT4, SOX2, and KLF4, to regulate CSC self-renewal and maintenance [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that FOXM1 plays a critical role in maintaining the CSC self-renewal and tumorigenic potential [28], and FOXO3a can bind to the promoter of FOXM1 to suppress its transcription [29,30]. Therefore, we evaluated whether FOXO3a affects BCSC properties by controlling FOXM1 signaling.…”
Section: Foxo3a Suppresses Bcsc Properties Via Inhibition Of Foxm1mentioning
confidence: 99%
“…AURKA has been studied in a wide range of human malignancies and is associated with poor prognosis in several malignancies, including cervical squamous cell carcinoma, hepatocellular carcinoma, and nonsmall cell lung carcinoma (Ma et al, ; Wang et al, ; Zheng et al, ). Besides, Yang et al, () reported that AURKA as a transactivating co‐factor in the induction of the c‐Myc oncoprotein in breast cancer stem cells (BCSCs). In CRC, AURKA is critical for chromosome 20q amplification‐associated malignant transformation in colorectal adenomas (Chuang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…FOX subclass M1 (FOXM1), an oncogenic transcription factor involved in drug resistance, is regulated downstream of PI3K-AKT and MAPK-ERK and activates AURKA expression. In turn, AURKA functions as a cofactor allowing kinase-independent transactivation of FOXM1 target genes (45).…”
Section: Discussionmentioning
confidence: 99%